148k views
5 votes
Simplify (1-√3)(⅓+√3) leaving your answer in the form p+q√3​

1 Answer

4 votes

Answer:


(-8 +2√(3) )/(3)

Explanation:

When working with surds we need to take note of the roots present there.

To expand this equation we can do it the following way noting that √3 X √3 = 3

Expanding (1-√3)(⅓+√3)

1 X 1/3 = 1/3

1 X √3 = √3

-√3 X 1/3 =-√3/3

√3 X √3 = 3

hence, expanding the equation, we have

1/3 + √3 -√3/3 + 3

We can simply group the like terms and add them up.

[1/3 +3] +[√3-√3/3]

10/3 +
(2√(3) )/(3)

=
(-8 +2√(3) )/(3)

User Fabian Sievert
by
5.6k points